Financing coal-fired power plant to demonstrate CCS (carbon capture and storage) through an innovative policy incentive in China. (November 2021) - Yang, Lin; Xu, Mao; Fan, Jingli; Liang, Xi; Zhang, Xian; Lv, Haodong; Wang, Dong
Abstract: Traditional policy incentives for carbon capture and storage (CCS) mainly rely on fiscal subsidies, which tend to put an inordinate strain on public finances. This study attempts to explore a non-fiscal incentive policy, granting a time extension (extra electricity quota), to finance early CCS demonstration projects in China. We find that coal-fired power plant (CFPP) operate at a loss even without CCS retrofitting under the current electricity quota (4000 h per year), while it can make profits with CCS retrofitting if extra electricity quotas are provided. Specifically, the electricity quota needs to be roughly 4709–7260 h per year with the CO2 capture level ranging from 0.1 to 1 Mt per year in the demonstration stage. In particular, the levelized cost of electricity (LCOE) of CFPP with a capture level of 1 Mt per year is estimated at 298.8 CNY/MWh if the electricity quota reaches 7000 h per year, which is approximately equal to that of CFPP without CCS retrofitting and extra electricity quota (292.2 CNY/MWh). Thus, the extra electricity quota can be considered as an economically feasible policy incentive, and related results are able to provide useful information for electric power enterprises and government decision-makers. Highlights: Extra electricity quota is proposed as an incentives mechanism for CCS project. The NPV and LCOE are estimated under different electricity quotas. Carbon trading can reduce the power generation cost to some extent. The critical conditions are discussed in various scenarios. The effects of changes in parameters are estimated through sensitivity analysis.